New approach addressing sustainability in urban areas using sustainable city models - Barbosa, José Amarilio (2014)
A brief analysis of the environmental, social and economic paradigm of nowadays cities, allows reaching a simple conclusion: current cities are not sustainable. Considering this, it is very important to study the causes of cities problems and to develop city models implementing sustainability practices. There are a limited number of studies developing sustainable city models, but the scientific community lacks even more studies about the rehabilitation of current cities to implement these models. This work emerges with the objective of analysing how it is possible to implement sustainability practices in cities through the development of a sustainable city model and an urban rehabilitation plan. The development of sustainable city models is a very complex topic and the analysis of the literature shows that it is necessary to consider the relation between environmental and social aspects in the development of sustainable cities, while taking special concerns when considering the economic issues. It was also concluded that sustainable city models and rehabilitation plans should be subject to sustainability assessments and should consider the active participation of its inhabitants. In fact, a city can only be sustainable if its population is in harmony with the city model and we can only assess results by predicting and measuring performance levels.